Public Sector Dispute Resolution : An American Twist to a Canadian Approach - Ponak, Allen (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1976)
The objective here is to report on the experiences of the Special Committee on Collective Bargaining Impasses in Public Employment and to emphasize how the various parties viewed the impasses procedures then in effect and what kinds of revisions they considered most desirable.